3
$\begingroup$

$\sqrt{9+6\sqrt{2}}$ to find length

But how do I express the above in the form of $\sqrt{c} + \sqrt{d}$.

$\endgroup$
  • 2
    $\begingroup$ Try to see what happens computing $(\sqrt{c}+\sqrt{d})^2$; what do they need to be to get what you want? $\endgroup$ – pjs36 Sep 21 '15 at 22:57
  • $\begingroup$ With what restrictions on $c$ and $d$ ? Without restrictions, you just take $d=0$ and $c= 9+6\sqrt{2}$. $\endgroup$ – lhf Sep 22 '15 at 0:06
  • $\begingroup$ You can find several similar question on this site. For example, this one. $\endgroup$ – Martin Sleziak Mar 25 '16 at 9:59
1
$\begingroup$

Hint: $$9+6\sqrt{2}=6+6\sqrt{2}+3=(\sqrt{6}+\sqrt{3})^2$$

$\endgroup$
1
$\begingroup$

Let the side of the square be $(\sqrt c+\sqrt d)$ then its area is given as $$(\sqrt c+\sqrt d)^2=9+6\sqrt 2\tag 1$$ $$c+d+2\sqrt{cd}=9+6\sqrt 2$$ by comparing the corresponding rational & irrational parts, we get $$c+d=9\tag 2$$ $$2\sqrt{cd}=6\sqrt 2\tag 3$$ Now, we know $$(\sqrt c-\sqrt d)^2=(\sqrt c+\sqrt d)^2-2\sqrt{cd}$$$$=(9+6\sqrt 2)-2(6\sqrt 2)$$$$(\sqrt c-\sqrt d)^2=9-6\sqrt 2\tag 4$$ multiplying (1) & (4) we get $$(\sqrt c+\sqrt d)^2(\sqrt c-\sqrt d)^2=(9+6\sqrt 2)(9-6\sqrt 2)$$ $$(c-d)^2=9\implies c-d=\pm 3$$ 1. taking positive sign, we get $c-d=3\tag 5$ solving (2) & (5), we get $$\color{red}{c=6, \ d=3}$$ 2. taking negative sign, we get $c-d=-3\tag 6$ solving (2) & (6), we get $$\color{red}{c=3, \ d=6}$$ Both the above cases give the same result. Hence, the side of the square is $$\color{red}{\sqrt c+\sqrt d}=\color{blue}{\sqrt 6+\sqrt 3}$$ or $$\color{red}{\sqrt c+\sqrt d}=\color{blue}{\sqrt 3+\sqrt 6}$$

$\endgroup$
  • $\begingroup$ Why can you compare just the corresponding rational an irrational parts? $\endgroup$ – lhf Sep 22 '15 at 0:03
  • $\begingroup$ Because it is an equality/equation. So corresponding rational & irrational parts should be equal $\endgroup$ – Harish Chandra Rajpoot Sep 22 '15 at 0:07
  • 2
    $\begingroup$ From (3) we get $cd=18$ and we can then solve a simple quadratic for $c,d$ by inspection. $\endgroup$ – lhf Mar 25 '16 at 10:12
0
$\begingroup$

Notice, let the side of the square be $a$ then its area is given as $$a^2=9+6\sqrt 2$$ $$a^2=9+2(3)\sqrt 2$$ $$a^2=9+2(\sqrt 3\sqrt 3)\sqrt 2$$ $$a^2=9+2(3)\sqrt 2$$ $$a^2=9+2(\sqrt 3\sqrt 2)(\sqrt 3)$$ $$a^2=6+3+2\sqrt{6}\sqrt 3$$ $$a^2=(\sqrt 6)^2+(\sqrt 3)^2+2(\sqrt{6})(\sqrt 3)$$ Using $a^2+b^2+2ab=(a+b)^2$, we get $$a^2=(\sqrt 6+\sqrt 3)^2$$ hence, side of square $$a=\color{red}{\sqrt6+\sqrt 3}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.